FIGURATIVE LANGUAGE IN THE ALBUM “GOOD LUCK TO YOU, GIRL SCOUT!” BY THE BLACK SKIRTS - Ave Lucia Nadeak (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2023)
Language allows humans to communicate by sending explicit or implicit messages. Figurative language is used to communicate indirectly in literature. A song that uses figurative language may confuse the listener with the meaning. This study investigated figurative language and the meaning of six songs from the album